2016
DOI: 10.1038/srep31756
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent jet flow generated downstream of a low temperature dielectric barrier atmospheric pressure plasma device

Abstract: Flowing low temperature atmospheric pressure plasma devices have been used in many technological applications ranging from energy efficient combustion through to wound healing and cancer therapy. The generation of the plasma causes a sudden onset of turbulence in the inhomogeneous axisymmetric jet flow downstream of the plasma plume. The mean turbulent velocity fields are shown to be self-similar and independent of the applied voltage used to generate the plasma. It is proposed that the production of turbulenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 27 publications
4
41
0
Order By: Relevance
“…The resulting temperature profile where the maximum is located downstream instead of at the exit of the capillary is often not incorporated in numerical models. This is important to take properly into account the effect of local heating in the modification of gas flow dynamic induced by plasma jet as discussed in 42,43 . The observed heat exchange was also present without any plasma (0 kV or 0 kHz) while still operating a constant 1 slm helium flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting temperature profile where the maximum is located downstream instead of at the exit of the capillary is often not incorporated in numerical models. This is important to take properly into account the effect of local heating in the modification of gas flow dynamic induced by plasma jet as discussed in 42,43 . The observed heat exchange was also present without any plasma (0 kV or 0 kHz) while still operating a constant 1 slm helium flow.…”
Section: Discussionmentioning
confidence: 99%
“…However when the plasma is on, the rising of the flow at a given distance is less than without plasma (about 1 mm instead of 1.8 mm without plasma at 16 mm distance from the nozzle). The modification of the gas flow dynamics by the plasma is a well known fact and several observations have been made stressing the importance of heating and/or ion wind, causing these changes in the helium flow 42,[44][45][46][47][48] . No consensus has been reached yet whether heating or ion-wind is dominant.…”
Section: Discussionmentioning
confidence: 99%
“…Oil with a nominal size of 1 µm was used to seed the air within the enclosure. The Stokes numbers of the seeding particles used throughout the study was < 0.1, thus ensuring that the seeding particles followed the fluid flow closely with tracing errors being < 1%  20,21 . The velocity vectors were computed on a square grid with spatial resolution of 56 µm using a recursive cross-correlation technique.…”
Section: Methodsmentioning
confidence: 99%
“…It has been widely reported that the generation of plasma in a buoyant axisymmetric jet configuration leads to a rapid transition from laminar to turbulent flow. [6][7][8][9][10] It is commonly assumed that gas heating and electrohydrodynamic (EHD) forces play a role in creating turbulence within the flowing gas channel, with the latter being considered as the dominant mechanism. Indeed, Park et al [11] used a pulsed plasma jet to demonstrate that EHD forces are primarily exerted by space charge drifting in the applied electric field following streamer propagation, confirming the modeling results of Hasan and Bradley.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…[12] Whalley and Walsh demonstrated that the spatially developing velocity fields in an inhomogeneous axisymmetric plasma jet flow are turbulent and self-similar, with characteristics matching the turbulent velocity fields which develop naturally with increasing distance from the jet exit. [8] Using an order-ofmagnitude analysis, it was predicted that the presence of a discharge should only increase the jet exit velocity by approximately 10%. Many studies in the field of fluid dynamics have indicated that the generation of turbulence in an axisymmetric jet flow is related to smallamplitude body forces causing perturbations in the unstable shear layers at the jet exit, which grow as they move downstream.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%